2022
DOI: 10.1063/5.0112993
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz high-Q magnetic dipole resonance induced by coherent Fano interactions

Abstract: High Q-factor resonance holds great promise for bio-chemical sensing and enhanced light–matter interaction. However, terahertz (THz) magnetic resonances usually demonstrate low Q-factors, resulting in huge energy radiation loss particularly in high frequency bands. Here, we show that high Q-factor magnetic dipole resonance at THz frequencies can be achieved by exploiting the coherent Fano interactions with strong field enhancements in an array composed of single metallic split-ring resonators, working at Wood–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Periodic boundary conditions in both x and y directions along with perfectly matched layer is the z direction are applied to the metamaterial unit cell. Theoretical simulation techniques can be supported in recent papers [21,22,31]. The filtering properties of the resonator can occur normally when an infinite metasurface is fabricated into a finite sample [21,22,31].…”
Section: Metasurface Design and Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic boundary conditions in both x and y directions along with perfectly matched layer is the z direction are applied to the metamaterial unit cell. Theoretical simulation techniques can be supported in recent papers [21,22,31]. The filtering properties of the resonator can occur normally when an infinite metasurface is fabricated into a finite sample [21,22,31].…”
Section: Metasurface Design and Simulationmentioning
confidence: 99%
“…Theoretical simulation techniques can be supported in recent papers [21,22,31]. The filtering properties of the resonator can occur normally when an infinite metasurface is fabricated into a finite sample [21,22,31]. The relative permittivity of gold is calculated by the Drude model as ε = 1-ω p 2 /(ω 2 +iγ c ω) in the THz regime, with plasma frequency ω p = 1.37 × 10 16 rad/s and damping rate γ c = 4.08 × 10 13 rad/s [22,32,33].…”
Section: Metasurface Design and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This resonant behavior offers potential applications in various fields, including sensing, optical filtering, and nonlinear optics. Previous studies have indicated that the geometric parameters of the unit structure influence the Fano resonance [4][5][6][7]. Thus, the optimum design of these unit structures plays a crucial role in both generating and modulating the Fano resonance.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Enhanced manipulation of terahertz waves and the response of their elds to matter is possible by combining multiple materials and designing different cell structures. 13 Metamaterial-excited Fano resonance has become an important research direction. [14][15][16][17] With the development of tunable materials, such as graphene and VO 2 , multifunctional sensors based on metamaterials have progressed signicantly.…”
Section: Introductionmentioning
confidence: 99%